Meningkatkan Pemahaman Siswa Kelas V SDN Mekarjaya pada Materi Perbandingan dan Skala dengan Model Pembelajaran Jigsaw - Suanto, Babam Eko (Didaktika, 2021)
Learning mathematics is usually very feared by students because students think that mathematics is difficult. Therefore, teachers must be creative and innovative in teaching mathematics so that students enjoy the mathematics subject. If students already enjoy mathematics subjects, students will automatically be enthusiastic in the learning process which has an impact on satisfying student learning outcomes. Some of these conditions were also found at the State Elementary School of Mekarjaya, especially in terms of scale. To overcome this, teachers must use a learning model that is fun and follows the characteristics of the material to be taught, one of which is the jigsaw learning model in learning mathematics on comparison and scale material. This research is in the form of classroom action research which aims to improve learning conditions. The research subjects are fifth-grade students in the even semester of 2020/2021. Based on the results of the study, there was an increase in the learning outcomes of fifth-grade students at State Elementary School of Mekarjaya, Takokak District, Cianjur Regency from pre-cycle, cycle I, and cycle II. In the pre-cycle, only 5 people completed 20 students, or 25% who reached the standard minimum score. In cycle 1 there was an increase of 13 students who completed from 20 students or 65% who reached the standard minimum score and in cycle 2 it increased again to 20 students from 20 students who completed or 100% who reached the standard minimum score. This shows that the jigsaw model is effective in improving students' ability to master comparison and scale material.